Peran Digital Parenting dalam Komunikasi Interpersonal antara Orang Tua dengan Anak Usia 2-5 Tahun di Rt 005/Rw 007 Perumahan Gunung Anyar Emas (Jurnal Insan Pendidikan dan Sosial Humaniora, 2024)
Parenting or parenting is a relationship between parents and children who are close and share effective parenting models. Technological advances in the era of globalization have greatly influenced the parenting process which is no longer limited to local culture. Various problems arise related to parenting and communication between parents and children. Interpersonal communication is communication carried out in two directions individually or in groups which elicits responses from both. This research aims to describe the application of digital parenting concepts by parents to children aged 2 -5 years in RT005/RW 007 Gunung Anyar Emas Housing Complex and determine the role of digital parenting in interpersonal communication between parents and children aged 2 -5 years. The method used is qualitative with a descriptive analysis approach. The subjects studied were parents and children aged 2-5 years, totaling 5 people who implemented digital parenting. The research results showed that the application of the digital parenting concept includes: 1) implementing rules and agreements in using gadgets; 2) guiding and accompanying children; 3) use child mode as parental control; 4) balance children's play time. In this way, interpersonal communication between parents and children develops as expected. This means that children's use of gadgets does not have a negative effect. This cannot be separated from the role of parents in caring for children digitally.